Crystal plasticity finite element method application in micro/meso-scaled deep drawing and some related concerns - Tong Xu; Fu M. W. (MATEC Web of Conferences)
The crystal plasticity finite element method (CPFEM) has been widely used in the research of micro/meso-scaled deformation of materials. In this talk, the effectiveness of CPFEM in simulating deep drawing processes is highlighted, with a particular focus on modelling complex stress distributions and capturing the effects of material anisotropy and thickness variations. It is found that CPFEM can accurately depict the influence of material properties on formability at these scales. However, the computational cost, the requirement for improved material models to handle deep drawing, and the variety of modelling features for different materials and processes are some serious concerns, which are elucidated in this talk, and the importance of CPFEM in predicting and analysing the precision and efficiency of micro/meso-scaled deep drawing is highlighted.